Let f=z("p^2+q^2)+px+qy"
Using charpit's method,
"\\frac{dz}{-p\\frac{df}{dp}-q\\frac{df}{dq}}" ="\\frac{dp}{\\frac{df}{dx}+p\\frac{df}{dz}}" ="\\frac{dq}{\\frac{df}{dy}+q\\frac{df}{dz}}=\\frac{dx}{\\frac{-df}{dp}}=\\frac{dy}{\\frac{-df}{dq}}"
From second and third factor we have
"\\frac{dp}{\\frac{df}{dx}+p\\frac{df}{dz}}=\\frac{dq}{\\frac{df}{dy}+q\\frac{df}{dz}}"
"\\frac{dp}{p+p(p^2+q^2)}=\\frac{dq}{q+q(p^2+q^2)}"
"\\frac{dp}{p}=\\frac{dq}{q}"
So by integrating ,we get
"log(p)=log(q)-log(a)"
q=pa
Putting the value of p in given equation,
"p^2(1+a^2)z+px+apy=0"
"p(1+a^2)z+(x+ay)=0"
so p="-\\frac{x+ay}{z(1+a^2)}" so q="-\\frac{a(x+ay)}{(1+a^2)z}"
now we have to solve
dz=pdx+qdy
"dz=-\\frac{x+ay}{(1+a^2)z}dx-\\frac{a(x+ay)}{1+a^2)z}dy"
"(1+a^2)zdz=-xdx-a(ydx+xdy)-a^2ydy"
On integrating the above equation, we get
"(1+a^2)\\frac{z^2}{2}=-\\frac{x^2}{2}-axy-a^2\\frac{y^2}{2}"
"(1+a^2)z=-x^2-2axy-a^2y^2"
This is the solution.
Comments
Leave a comment